Relativistic eikonal formalism applied to inclusive quasielastic proton-induced nuclear reactions - Titus, Nortin, P-D (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Physics))--University of Stellenbosch, 2011.